2009
DOI: 10.1021/np800455b
|View full text |Cite
|
Sign up to set email alerts
|

An Endophytic Fungus from Camptotheca acuminata That Produces Camptothecin and Analogues

Abstract: The pentacyclic quinoline alkaloid camptothecin (1) is a potent antineoplastic agent. Two of its analogues, 9-methoxycamptothecin (2) and 10-hydroxycamptothecin (3), exhibit similar potency but do not have the potential therapeutic drawbacks produced by unmodified 1. We have established methodology for the isolation and unequivocal identification and characterization of a novel endophytic fungus isolated from the inner bark of the medicinal plant Camptotheca acuminata, which produced 1-3 in rich mycological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
195
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(201 citation statements)
references
References 26 publications
4
195
0
2
Order By: Relevance
“…To establish the production pattern of CPT over successive generations, the axenic CPT-producing fungal isolates were subcultured from the first generation to its following generations by using the hyphal tip method (Kusari et al 2009). The strains of each generation were fermented, extracted, and analyzed, following the same procedure described above.…”
Section: Successive Subculturing Of Cpt-producing Endophytic Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…To establish the production pattern of CPT over successive generations, the axenic CPT-producing fungal isolates were subcultured from the first generation to its following generations by using the hyphal tip method (Kusari et al 2009). The strains of each generation were fermented, extracted, and analyzed, following the same procedure described above.…”
Section: Successive Subculturing Of Cpt-producing Endophytic Fungimentioning
confidence: 99%
“…Successive subculturing of CPT-producing endophytic fungi Previous works (Kusari et al 2009;Gurudatt et al 2010) suggested that CPT production will be attenuated with subsequent successive subculturing. We performed successive subculturing of CPT-producing LY341, LY355, and LY357 to seek for CPT-producing strains with steady CPT production.…”
Section: Hplc-dad Screening and Hplc-dad-hrms Verification Of Cpt-promentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytes may contribute to protecting their host plant from diseases by producing a diverse array of secondary metabolites such as terpenoids, palmarumycins, furandiones, phenols, dimeric anthrone and benzopyroanone (Schulz et al 2002; Porras-Alfaro and Bayman 2011). Moreover, endophytes comprise a promising rich source of potential bioactive medicinal constituents such as podophyllotoxin (Canel et al 2000), paclitaxel (Taxol) (Stierle et al 1993), hypericin (Kusari et al 2008) and camptothecin (Kusari et al 2009). Generally, medicinal plants used in traditional medicine are selected for surveying bioactive endophytic fungi due to documented beneficial applications (Kaul et al 2012; Kusari et al 2013) and thus, high likelihood of producing pharmaceutically important secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, subsequent isolates can be considered as true endophytic fungi (Barnett and Hunter 1956). Earlier studies also define the successful surface sterilization process for the isolation of endophytes with no contamination of epiphytes (Kusari et al 2009; Lin et al 2010). The isolated endophytic fungus was then identified as Gliomastix sp.…”
Section: Resultsmentioning
confidence: 99%